Receptive Fields of Visual Neurons: The Early Years. (November 2014) - Spillmann, Lothar
This paper traces the history of the visual receptive field (RF) from Hartline to Hubel and Wiesel. Hartline (1938, 1940) found that an isolated optic nerve fiber in the frog could be excited by light falling on a small circular area of the retina. He called this area the RF, using a term first introduced by Sherrington (1906) in the tactile domain. In 1953 Kuffler discovered the antagonistic center—surround organization of cat RFs, and Barlow, Fitzhugh, and Kuffler (1957) extended this work to stimulus size and state of adaptation. Shortly thereafter, Lettvin and colleagues (1959) in an iconic paper asked "what the frog's eye tells the frog's brain". Meanwhile, Jung and colleagues (1952–1973) searched for the perceptual correlates of neuronal responses, and Jung and Spillmann (1970) proposed the term perceptive field (PF) as a psychophysical correlate of the RF. The Westheimer function (1967) enabled psychophysical measurements of the PF center and surround in human and monkey, which correlated closely with the underlying RF organization. The sixties and seventies were marked by rapid progress in RF research. Hubel and Wiesel (1959–1974), recording from neurons in the visual cortex of the cat and monkey, found elongated RFs selective for the shape, orientation, and position of the stimulus, as well as for movement direction and ocularity. These findings prompted the emergence in visual psychophysics of the concept of feature detectors selective for lines, bars, and edges, and contributed to a model of the RF in terms of difference of Gaussians (DOG) and Fourier channels. The distinction between simple, complex, and hypercomplex neurons followed. Although RF size increases towards the peripheral retina, its cortical representation remains constant due to the reciprocal relationship with the cortical magnification factor (M). This constitutes a uniform yardstick for M-scaled stimuli across the retina. Developmental studies have shown that RF properties are not fixed. RFs possess their full response inventory already at birth, but require the interaction with appropriate stimuli within a critical time window for refinement and consolidation. Taken together these findings paved the way for a better understanding of how objective properties of the external world are encoded to become subjective properties of the subjective, perceptual world.